Environmental oversight and the citizen activist: Lessons from an oral history of activism surrounding Elmira, Ontario's 1989 water crisis. Issue 1 (1st January 2017) - Case, Robert A.
Abstract: In this article, the author presents an oral history of community-based water activism in Elmira, Ontario, Canada, and draws insights from it for theory and praxis in community organization. In 1989, a group of citizens calling themselves "APT Environment" came together over a concern about chemical pollution in their community that eventually triggered the closure of municipal drinking water wells. Organizing themselves and building capacity within the group, these grassroots citizens pushed for action against considerable backlash, and emerged as a significant player in the ongoing struggle to mitigate further contamination, to have the contamination remediated, and to see environmental justice served. The story of APT Environment is one of shifting activist identities that evolve with a shifting political context. Drawing on this oral history, the author offers implications for social movement theory and for community organizing in other contexts.